Threatening the heart and mind of gender stereotypes: Can imagined contact influence the physiology of stereotype threat?. (January 2016) - Allen, Ben; Friedman, Bruce H.
Abstract: Research shows that when a gender stereotype is made salient and the target of the stereotype is asked to perform in the stereotyped domain, targets of the stereotype often perform at a lower level compared to situations when the stereotype was not made salient. The noticeable absence of female faculty and students in math and science departments at coed universities throughout the United States may increase the belief in gender stereotypes and discourage women from pursuing careers in these fields. Contact with counterstereotypical exemplars, such as female science experts, decreases belief in gender stereotypes and increases women's motivation to pursue careers in science. Thus, the present study examined whether imagining an interpersonal interaction with a counterstereotypical exemplar removes the physiological and performance effects of stereotype threat. Subjects were asked to imagine either a nature scene or meeting a female math professor, and were also assigned to either a control or stereotype threat condition. Imagination was used because studies have shown it to be an effective method of simulating interpersonal contact. Subjects were 139 young women (mean age 19 years) recruited from a pool of undergraduates. Results showed that the stereotype threat manipulation elicited greater vagal withdrawal and poorer working memory capacity during the n ‐back, and that vagal withdrawal was attenuated when the stereotype threat manipulation was preceded by a brief imagined interaction with a counterstereotypical exemplar. This study provides novel evidence that exposure to counterstereotypical exemplars can diminish cardiovascular reactions to salient information about threatening gender stereotypes.